Isolation and Identification of Bacterial Strains with Fatty Acid Methyl Ester (FAME) Analysis - Kirthi, Pullannagari Sai; Naidu, Srinivasa; Kanchana, Parijatham (Asian Journal of Biological and Life Sciences)
Soil is an excellent source of micro-organisms, especially bacteria. In our present study, we isolated bacteria from a fertile agricultural soil IRCP (361) from Northern India and studied the morphological, cultural, and biochemical characteristics. We performed FAME (Fatty Acid Methyl Ester) analysis of the isolated strains. The isolated strains comprised of Gram- positive bacteria. Using FAME analysis, we confirmed majority of bacteria belong to Bacillus species and few belong to Pseudomonas species. Bacillus species enhance nitrogen fixation which increases soil fertility and protect plants from toxic effects of metals. Pseudomonas confers resistance against rootsecreted antibiotics. Paenibacillus species possess potentiality for bioremediation of xenobiotics. This study shows that the soil is fertile due to the abundance of the Nitrogen fixing bacteria and the identification of the bacteria is fast and accurate using FAME analysis.
Keywords: Bacillus species; FAME analysis; Gram-positive bacteria; Nitrogen fixation; Pseudomonas species; Soil fertility